Research on Application of 3D Simulation Technology in Industrial Product Design Technology. (14th July 2022) - Huang, Chenhan; Shi, Daijiao
Abstract : In order to study the driving effect of industrial product design, a method based on the application of 3D simulation technology in industrial product design technology was proposed. This method introduces the information about the change in industrial product design in industrial enterprises and analyzes the application of 3D simulation technology in industrial product design by taking DIALux, industrial robot, and resource information search system as examples. The results show that the application of 3D simulation system needs to be combined with industrial software, and the development of industrial software business mainly based on 3D simulation technology is emphasized so that the business revenue of enterprises increases from 709 million yuan in 2029 to 1.385 billion yuan in 2021, with a compound growth rate of 25.01%, which has achieved good economic benefits. 3D simulation technology plays an important role in promoting the development of industrial product design technology. It is necessary to actively promote the integration between 3D simulation technology and industrial software.